2021
DOI: 10.1016/j.breast.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II study to determine the optimal dose of 3-week cycle nab-paclitaxel in patients with metastatic breast cancer

Abstract: Background Chemotherapy-induced peripheral neuropathy is commonly observed in patients treated with nanoparticle albumin–bound paclitaxel (nab-PTX). We conducted a multicenter randomized controlled study to evaluate the optimal dose of nab-PTX. Methods We compared three different doses of q3w nab-PTX (Standard: 260 mg/m 2 [SD260] vs Medium: 220 mg/m 2 [MD220] vs Low: 180 mg/m 2 [LD180]) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Many of the QoL constituent domains showed a positive trend with low-dose nab-PTX, but SFWB showed the opposite trend, for unknown reasons. Primary endpoint analysis showed that intravenous administration of low-dose nab-PTX at 180 mg/m 2 q3w may be the optimal therapy with meaningful efficacy and favorable toxicity for patients with metastatic breast cancer [ 4 ]. The QoL substudy also showed that low-dose nab-PTX at 180 mg/m 2 q3w is optimal in terms of QoL and cancer-related fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the QoL constituent domains showed a positive trend with low-dose nab-PTX, but SFWB showed the opposite trend, for unknown reasons. Primary endpoint analysis showed that intravenous administration of low-dose nab-PTX at 180 mg/m 2 q3w may be the optimal therapy with meaningful efficacy and favorable toxicity for patients with metastatic breast cancer [ 4 ]. The QoL substudy also showed that low-dose nab-PTX at 180 mg/m 2 q3w is optimal in terms of QoL and cancer-related fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Then, if the estimated incidence rate of grade 3/4 neuropathy was > 10%, the other dose was dropped. Primary analysis showed that low-dose nab-PTX at 180 mg/m 2 q3w may be the optimal therapy with meaningful efficacy and favorable toxicity in patients with metastatic breast cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary endpoint analysis showed that intravenous administration of low-dose nab-PTX at 180 mg/m 2 q3w may be the optimal therapy with meaningful e cacy and favorable toxicity for patients with metastatic breast cancer [4]. The QoL substudy also showed that low-dose nab-PTX at 180 mg/m 2 q3w is optimal in terms of QoL and cancer-related fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Then, if the estimated incidence rate of grade 3/4 neuropathy was > 10%, the other dose was dropped. Primary analysis showed that lowdose nab-PTX at 180 mg/m 2 q3w may be the optimal therapy with meaningful e cacy and favorable toxicity in patients with metastatic breast cancer [4].…”
Section: Trial Registrationmentioning
confidence: 99%
“…Nab-paclitaxel improved the pathological complete response rate and event-free survival compared with traditional taxanes, and with acceptable toxicities (63). Current studies of nab-paclitaxel in breast cancer have focused on dose adjustment and combination regimens with other drugs (64)(65)(66)(67)(68). In conclusion, the application of nab-paclitaxel in breast cancer has gradually improved from second-line and above-to first-line and neoadjuvant therapy.…”
Section: Breast Cancermentioning
confidence: 99%